EROSION HAZZARD IN THE CATCHMENTS AREA OFXIROPOTAMOS RIVER - KASTORIA USING GEOGRAPHICAL INFORMATION SYSTEM - ΖΑΡΚΑΔΑΣ Π.; ΜΑΡΓΩΝΗ Σ.; ΨΙΛΟΒΙΚΟΣ ΑΡ.; ΔΑΛΕΖΙΟΣ Ν. (Bulletin of the Geological Society of Greece, 2005)
The hazard of erosion in the Xeropotamos river drainage basin on the eastern side of Kastoria lake is examined in this paper, through G.I.S. techniques (methodology).Eight levels of information were taken into account: The channel network, the Digital Elevation Model (DEM through TIN), the surface slope degree and orientation, the lithology, the vegetational cover, the rainfall distribution and the wind blown factors.The combination of the above levels of information allowed the production of two alternative erosional hazard assessment maps. One counts for equal and another counts for not equal influence of all the above factors in the model. The erosional capacity of Xeropotamos is reflected on the flatlands of the eastern side of Kastoria lake,where the river deposits heavy sediment loads, thus forming a deltaic lobe into the lake. It threatens to split the lake, unless antierosional measures on the drainage basin reduces its capacity.